A comparative investigation between paclitaxel nanoparticle- and nanocrystal-loaded thermosensitive PECT hydrogels for peri-tumoural administration. Issue 44 (1st November 2016) - Lin, Zhiqiang; Xu, Shuxin; Gao, Wei; Hu, Hongxiang; Chen, Meiwan; Wang, Yitao; He, Bing; Dai, Wenbing; Zhang, Hua; Wang, Xueqing; Dong, Anjie; Yin, Yuxin; et al.
Abstract : Nanocrystal-based thermo-sensitive hydrogels release drugs more efficiently than nanoparticle-based gels. Abstract : For in situ thermosensitive hydrogels, it is a big challenge to achieve high drug loading, long-term local retention, and effective drug release simultaneously. To address these issues, we combined the strategy of drug nanocrystals (NCs) and thermosensitive hydrogels with higher gel strength. In particular, we developed paclitaxel NC-based hydrogels using PECT, a thermosensitive polymer synthesized by us (PTX-NC-PECT), and a nanoparticle-based system was used as the control (PTX-NP-PECT). First, high levels of PTX could be loaded in both PECT hydrogels. Moreover, in vivo near infrared fluorescence (NIRF) imaging showed that both hydrogel systems were able to maintain the payloads of 1, 1-dioctadecyltetramethyl indotricarbocyanine iodide (DiR) at a peri-tumoural site for at least 21 days, much longer than that achieved with the control hydrogel of Pluronic® F127. Furthermore, we observed that PTX-NCs released free PTX more effectively and homogeneously than PTX-NPs in vitro . It was further verified in vivo that the release of DiR from DiR-NC-PECT was more complete than that from DiR-NP-PECT. Finally, PTX-NC-PECT gel demonstrated the strongest anti-tumour efficacy on MCF-7 breast cancer. In conclusion, PTX-NC-PECT hydrogel might be a high-performance thermosensitive hydrogel for local cancer therapy.